Mobile Number Portability - Stefan Buehler; Justus Haucap (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
This paper examines the consequences of introducing mobile number portability (MNP). As MNP allows consumers to keep their telephone number when switching providers, it reduces consumers' switching costs. However, MNP may also cause consumer ignorance if telephone numbers no longer identify networks. As a result, while fostering competition for mobile customers, MNP may also induce operators to increase termination charges for calls to mobile networks, gener-ating ambiguous welfare effects. We examine how extensions such as MNP based on call-forwarding, termination fee regulation, and alternative means of carrier identification affect these findings.
urn:nbn:de:gbv:705-opus-1508
Keywords: L13; L96; L51; 330; number portability; switching costs; telecommunications; network competition; Mobiltelefon; Telekommunikation; Wettbewerb; Theorie